Impulse Buying Produk Kartu Perdana Xl Di Semarang - Camilus Isidorus Ikut; Intan Kartika (Serat Acitya, 2021)
This research was motivated by the company increasing competition in the mobile phone operator in Indonesia. This affects the Prime XL card sales which fluctuated during the years 2016-2018.This study was conducted to determine how to analyze the influence of the brand influence impulse buying prepaid cards XL in Semarang. In this study the authors used below the line and positive emotions as independent variables to be studied how they affect impulse buying. This study using multiple linear regression analysis using SPSS. The population is XL event at Superindo Candi in Semarang where the amount is not known for certain. The sample used as many as 100 people with engineering sample selection of non-probability sampling using accidental sampling. The research sample was determined by purposive sampling technique. Analysis of the data obtained in multiple linear regression analysis, hypothesis testing t test results showed that each - each variable below the line and positive emotions partially influence and significant to the variable impulse buying.